If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2x + 5 + 4x + -7 = 0 Reorder the terms: 5 + -7 + x + 2x + 4x = 0 Combine like terms: 5 + -7 = -2 -2 + x + 2x + 4x = 0 Combine like terms: x + 2x = 3x -2 + 3x + 4x = 0 Combine like terms: 3x + 4x = 7x -2 + 7x = 0 Solving -2 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = 0 + 2 7x = 0 + 2 Combine like terms: 0 + 2 = 2 7x = 2 Divide each side by '7'. x = 0.2857142857 Simplifying x = 0.2857142857
| 14=-2(x-3)+4 | | 8-7y=-34 | | -1/4x+15=-5 | | 3a+4b+2c=40 | | 9+(-4)x=13 | | -2(y-2)+3(4+3y)=-5 | | 9x^2+6=3x | | -2lx+3l=-60 | | 2xsquared+4x=0 | | 4b+18+3b=74 | | -54-9b-2b=-10 | | 3/i-9 | | 40+x=5.00 | | 6p-2=10(p-2)-4(14-4p)-6 | | x^17=x^15 | | 16=16+4x | | 10x^6-53x^4+36x^2=0 | | Y-26/9=5/6 | | 7x-4=5-8x | | (6x+1)-(5x-17)-(9x-24)=180 | | =x^4+3x^3-21x^2-33x+110 | | 6x+6(x-4)=9+4x | | 36=-40-2x | | f(-2x)=1.5x+12 | | f(x)=x^4+3x^3-21x^2-33x+110 | | 11/2•3 | | 2x+8-2x-8=0 | | y^2-2y-8x-7=0 | | F(2)=9x-5 | | -3-25a=15 | | 9(3z-1)=18z+45 | | 9(3z-1)=18z+45 |